Alpha thalassemia gene mutations in neonates from Mazandaran, Iran, 2012. Issue 4 (June 2014) - Jalali, Hossein; Mahdavi, Mohammad Reza; Roshan, Payam; Kosaryan, Mehrnoush; Karami, Hosein; Mahdavi, Mehrad
<x content-type="archive" xml:space="preserve">Abstract</x> Aim Alpha thalassemia is one of the most prevalent disorders worldwide and carrier frequency of the disease is varied in different parts of the world. Although different studies in Iran and Mazandaran province have been carried out to identify different mutations of alpha globin gene among people with low hematological indices, frequencies of these mutations were unknown in general population, and thus the aim of this study was to evaluate the carrier frequencies of alpha globin gene mutations among neonates in Mazandaran. Material and methods Four hundred and twelve neonates were collected from a delivery ward of a hospital in Sari. DNA was extracted from their cord blood samples using phenol-chloroform-based method. For the detection of five common alpha thalassemia gene mutations, multiplex-GAP-PCR and PCR-RFLP methods were applied. Results Sixty three (15.29%, confidence interval, CI 95%: 11.81–18.77) of investigated neonates had at least one of the five evaluated mutations. The -α3.7 deletion had the highest frequency (9.7%, CI 95%: 6.84–12.56) and none of the neonates had –Med double gene deletion. The -α4.2 deletion, αααanti3.7 triplication, and α−5nt mutations had frequencies of 4.1% (CI 95%: 2.19–36.01), 2.2% (CI 95%: 0.78–3.62), and 0.49% (CI 95%: −0.18–1.16), respectively. Discussion Our study showed that in most of the alpha thalassemia carriers just one copy of alpha globin gene was absent and they are not at risk of having children with Hb H disease or hydrops fetalis; however, up to 2.2% of neonates were carriers for αααanti3.7 triplication and they will be at risk for having a child with thalassemia intermediate if they marry a person which is a carrier of beta thalassemia.